PENGARUH GOOD CORPORATE GOVERNANCE, KEPUTUSAN PENDANAAN, KEPUTUSAN INVESTASI DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN PROPERTY DAN REAL ESTATE YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2022-2024 - Lenni Sinaga; Dompak Pasaribu; Selamat Siregar (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study analyzes the influence of institutional ownership, debt to equity ratio, total asset growth, and return on asset on firm value proxied by Tobin's Q in property and real estate companies listed on the Indonesia Stock Exchange for the period 2022-2024. The research method used is a quantitative method with secondary data from companies' annual financial reports. The data analysis technique used is multiple linear regression analysis with the assistance of SPSS version 27 program. The results show that partially, Good Corporate Governance proxied by institutional ownership has a negative and insignificant effect on firm value. Funding decisions proxied by debt to equityratio have a positive and significant effect on firm value. Investment decisions proxied by total asset growth have a negative and insignificant effect on firm value, and profitability proxied by return on asset has a negative and insignificant effect on firm value. Simultaneously, Good Corporate Governance, funding decisions, investment decisions, and profitability have a significant effect on firm value measured by Tobin's Q.